Pengaruh Faktor Ekonomi Terhadap Kinerja Perbankan Syariah: Program Edukasi Dan Penguatan Kepercayaan Nasabah - Hasrah, A. Rosmini; Risnawati, Risnawati; Lisnawati, Lisnawati; Sani, Chaerul (Yayasan Habiburrahman Jamalu Bina Ummat, 2025)
This PKM aims to educate and strengthen customer trust in the performance of Islamic banking. This program aims to improve public literacy regarding Islamic banking products and services while strengthening customer trust through education and direct approaches in certain areas. The results of the PKM show that 1) The Influence of Macroeconomic Factors on Islamic Banking Performance: Economic Growth, Inflation and Interest Rates (BI Rate or Equivalent). 2) The Influence of Microeconomic Factors on Islamic Banking Performance: Capital Capacity, Asset Quality and Operational Efficiency. 3) The Impact of Government Policies and Regulations: The Role of Financial Authorities and Islamic Financial Instruments. 4) The Socio-Economic Role of Society: Public Awareness and Preferences as well as Public Purchasing Power and Consumption. Thus, customer trust in Islamic banking can increase, which will ultimately encourage the contribution of Islamic banking to local economic growth.